Domain of applicability of various approaches to description of electromagnetic field in medium - Lyagushyn, S.F.; Sokolovsky, A.I.; Salyuk, Yu.M. (Вопросы атомной науки и техники, 2012)
The problem of parameters, which are necessary for nonequilibrium electromagnetic field description, is investigated on the basis of the Bogolyubov reduced description method establishing the necessity of binary correlations in the minimal set of parameters taken into account in evolution equations. The corresponding theory can be built in terms of one-particle density matrices, Wigner distribution functions, simultaneous correlation functions of field operators, and generating functionals. The obtained results can be analyzed with the help of approaches elaborated in quantum optics. Various methods in theoretical and experimental research into field correlations are compared. Проблема параметров, которые необходимы для описания неравновесного электромагнитного поля, исследуется на основе метода сокращённого описания Боголюбова, устанавливающего необходимость бинарных корреляций в минимальном наборе параметров, принимаемых во внимание в уравнениях эволюции. Соответствующая теория может быть построена в терминах одночастичных матриц плотности, вигнеровских функций распределения, одновременных корреляционных функций полевых операторов и производящих функционалов. Полученные результаты могут анализироваться с помощью подходов, разработанных в квантовой оптике. Сравниваются разные методы теоретического и экспериментального исследования корреляций поля. Проблема параметрів, необхідних для опису нерівноважного електромагнітного поля, досліджується на основі методу скороченого опису Боголюбова, що встановлює необхідність бінарних кореляцій у мінімальному наборі параметрів, які беруться до уваги в рівняннях еволюції. Відповідна теорія може бути побудована мовою одночастинкових матриць густини, вігнерівських функцій розподілу, одночасних кореляційних функцій польових операторів і твірних функціоналів. Отримані результати можуть бути проаналізовані за допомогою підходів, розроблених у квантовій оптиці. Порівнюються різні методи теоретичного й експериментального дослідження кореляцій поля.